Guidance on the scientific requirements for health claims related to muscle function and physical performance: (Revision 1). (30th October 2018) - ,; Turck, Dominique; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; et al.
Abstract: EFSA has asked the Panel on Nutrition, Novel Foods and Food Allergens (NDA) to update the guidance on the scientific requirements for health claims related to physical performance published in 2012. The update takes into account the experience gained by the NDA Panel with the evaluation of additional health claim applications, changes introduced to the general scientific guidance for stakeholders for health claims applications and information collected from a grant launched in 2014 which aimed at gathering information in relation to claimed effects, outcome variables and methods of measurement in the context of the scientific substantiation of health claims. The guidance is intended to assist applicants in preparing applications for the authorisation of health claims related to muscle function and physical performance. The draft guidance was subject to public consultation from 16 July to 2 September 2018. This document supersedes the guidance on the scientific requirements for health claims related to physical performance published in 2012. It is intended that the guidance will be further updated as appropriate in the light of experience gained from the evaluation of health claims. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1495/full